2004
DOI: 10.1016/j.polymer.2004.10.052
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring bulk and surface grafting of poly(acrylic acid) in electron-irradiated PVDF

Abstract: International audienceEndowing conventional hydrophobic poly(vinylidene fluoride) (PVDF) films with hydrophilic properties was conducted using electron beam irradiation. Grafting of acrylic acid (AA) in/onto pre-irradiated PVDF films was investigated. Reaction parameters, monomer concentration and inhibitor concentration were examined. Radiation grafted films (PVDF-g-PAA) were synthesized with various grafting yields ranging from 12 to 130 wt % in presence of Mohr's salt (25 wt %). Below 80 wt % of monomer con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
64
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(71 citation statements)
references
References 31 publications
5
64
0
Order By: Relevance
“…7 We therefore attribute the 287 eV peak to CHACF n grafting points where the graft copolymers are bonded to fluorinated carbon atoms on the ePTFE surface. 36,37 This assignment is in agreement with this peak being of similar intensity for all the samples and the expected similar number of surface graft sites for all the samples as a result of using a constant radiation dose. …”
Section: Article Wileyonlinelibrarycom/appsupporting
confidence: 87%
See 3 more Smart Citations
“…7 We therefore attribute the 287 eV peak to CHACF n grafting points where the graft copolymers are bonded to fluorinated carbon atoms on the ePTFE surface. 36,37 This assignment is in agreement with this peak being of similar intensity for all the samples and the expected similar number of surface graft sites for all the samples as a result of using a constant radiation dose. …”
Section: Article Wileyonlinelibrarycom/appsupporting
confidence: 87%
“…On the other hand, Pulat and Eski 19 have shown that Q e values of cross linked P(AA-co-IA) hydrogels are very strongly dependent on pH, and that while at pH 5 2 a hydrogel with X AA 5 0.83 swelled to a greater extent than a pure PAA hydrogel, the order was reversed at pH 5 4, with the crossover at about pH 5 3. Furthermore, Pulat and Eski 19 have reported the equilibrium swelling of a series of P(AA-co-IA) hydrogels swollen in Britton-Robinson solution (pH 7.4) at 37 C and found that the copolymer hydrogels, which ranged in AA mole fraction from 0.66 to 1.00, swelled to a much smaller extent (fewer water molecules per hydroxyl group) than an PAA hydrogel prepared with the same cross linker concentration and this result correlates with our findings (see Table IV). The number of water molecules per carboxyl group for the samples given in Table IV are, however, smaller than those calculated from Katime and Rodriguez's data.…”
Section: Article Wileyonlinelibrarycom/appmentioning
confidence: 99%
See 2 more Smart Citations
“…However, PVDF is a hydrophobic polymer without any functional groups to promote cell adhesion on surface. Therefore, surface modification was widely applied to PVDF membranes to extend their applications as biomaterials [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%